Anxiety Status and Influencing Factors of Rural Residents in Hunan During the Coronavirus Disease 2019 Epidemic: A Web-Based Cross-Sectional Survey - Zhang, Yi; Chen, Yi-ping; Wang, Jianjian; Deng, Yanhong; Peng, Dezhen; Zhao, Liping (Frontiers in Psychiatry, 2020)
Objective: To explore the status quo of anxiety and its influencing factors among rural residents in Hunan Province during the coronavirus disease 2019 epidemic, and to provide an effective basis for prevention of and intervention for anxiety symptoms among rural residents. Methods: Convenience sampling was used. An online questionnaire was distributed to Hunan rural residents through the questionnaire star platform from February 26–29, 2020. The general data and anxiety of Hunan rural residents were investigated, and the data were analyzed using SPSS 18.0. Results: The mean Self-Rating Anxiety Scale score of 179 rural residents in Hunan was 40.93 ± 9.36. Based on the cutoff criteria, 32 residents had anxiety, including 26 with mild anxiety, five with moderate anxiety, and one with severe anxiety. The detection rate of anxiety was 17.88%. Self-rated health status, level of concern about the epidemic, and self-rated impact of the epidemic on one's life were the factors influencing the anxiety score of rural residents in Hunan (P < 0.05). Conclusion: During the coronavirus disease 2019 epidemic, the detection rate of anxiety in rural residents in Hunan was higher than that of the general population in China. The relevant departments should pay attention to the mental health of rural residents and implement targeted mental health prevention and intervention measures during the epidemic situation.